1999
DOI: 10.1103/physrevd.60.014004
|View full text |Cite
|
Sign up to set email alerts
|

Do the E866 Drell-Yan data change our picture of the chiral structure of the nucleon?

Abstract: We revisit the evaluation of the pionic mechanism of theū −d-asymmetry in the proton structure function. Our analysis is based on the extended AGK unitarity relation between contributions of different mechanisms to the inclusive particle production and the total photoabsorption cross-section (i.e. the proton structure function). We reanalyze the role of isovector reggeons in inclusive production of nucleons and Delta isobars in hadronic reactions. We find rather large contribution of reggeonexchange induced pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 38 publications
(44 reference statements)
4
66
0
2
Order By: Relevance
“…This calculation is typical of many of this type, in that the probability of finding the nucleon in a πN configuration is approximately twice that of finding it in the π∆ configuration [53,54]. However, a recent calculation by Nikolaev et al [55], also shown in Fig. 15, calls this into question.…”
Section: Origins Of the Nucleon Seamentioning
confidence: 87%
“…This calculation is typical of many of this type, in that the probability of finding the nucleon in a πN configuration is approximately twice that of finding it in the π∆ configuration [53,54]. However, a recent calculation by Nikolaev et al [55], also shown in Fig. 15, calls this into question.…”
Section: Origins Of the Nucleon Seamentioning
confidence: 87%
“…It was pointed out much earlier [8] that pionic fluctuations would create such a asymmetry in the sea and was subsequently calculated [9] before the experiments referenced above were carried out. Further, and of importance for what follows, the appearance of the flavor asymmetry at large values of x (0.1 < x < 0.25) indicates that the pions are fluctuated off the whole nucleon rather than off individual valence quarks [10][11][12], as would be the case in some versions of chiral perturbation theory (χ PT) [13]. While pions constitute a small fraction of the total sea, they have important consequences such as the asymmetry discussed above.…”
mentioning
confidence: 99%
“…The dominant role is played by the pion, which provides that d(x)/u(x) either increases monotonically with x or turns back towards unity too slowly [8,9]. Many explanations have been applied to attack this problem [10,11,12,13], such as effects of ∆ [10,11,12], the influence of the Pauli exclusion principle [12], adjustment of parameters [13], but none of these explanations provides a satisfactory description of the ratio d(x)/u(x). However, Alberg, Henley and Miller [14] found that the inclusion of the effect of the isoscalar vector meson ω, with a coupling constant g 2 ω /4π ≈ 8.1, allows a good description of the data.…”
mentioning
confidence: 99%